Nutritional status as marker for disease activity and severity predicting mortality in patients with systemic sclerosis. Issue 11 (28th May 2010) - Krause, Lijana; Becker, Mike O; Brueckner, Claudia S; Bellinghausen, Christina-Julia; Becker, Corinna; Schneider, Udo; Haeupl, Thomas; Hanke, Katharina; Hensel-Wiegel, Karin; Ebert, Heidrun; Ziemer, Sabine; Ladner, Ulf-Müller; et al.
Abstract : Objective: To assess and analyse nutritional status in patients with systemic sclerosis (SSc) and identify possible associations with clinical symptoms and its prognostic value. Methods: Body mass index (BMI) and parameters of bioelectrical impedance analysis (BIA) were assessed in 124 patients with SSc and 295 healthy donors and matched for sex, age and BMI for comparisons. In patients with SSc, BMI and BIA values were compared with clinical symptoms in a cross-sectional study. In a prospective open analysis, survival and changes in the nutritional status and energy uptake induced by nutritional treatment were evaluated. Results: Patients with SSc had reduced phase angle (PhA) values, body cell mass (BCM), percentages of cells, increased extracellular mass (ECM) and ECM/BCM values compared with healthy donors. Malnutrition was best reflected by the PhA values. Of the patients with SSc, 69 (55.7%) had malnutrition that was associated with severe disease and activity. As assessed by multivariate analysis, low predicted forced vital capacity and high N-terminal(NT)-proBNP values discriminated best between good and bad nutritional status. Among different clinical parameters, low PhA values were the best predictors for SSc-related mortality. BMI values were not related to disease symptoms or mortality. Fifty per cent of patients with SSc had a lower energy uptake related to their energy requirement, 19.8% related to their basal metabolism. Nutritional treatment improved the patients' nutritional status. Conclusions: In patients with SSc, malnutrition is common and not identified by BMI. BIA parameters reflect disease severity and provide best predictors for patient survival. Therefore, an assessment of nutritional status should be performed in patients with SSc.